2012
DOI: 10.4103/0019-5545.94644
|View full text |Cite
|
Sign up to set email alerts
|

Clinical profile and outcome of bipolar disorder patients receiving electroconvulsive therapy: A study from north India

Abstract: Background:Although electroconvulsive therapy (ECT) is used quite frequently among the bipolar patients in developing countries, very little data are available with regard to its effectiveness from the developing countries.Aim:A retrospective case note review was carried out of bipolar disorder patients who were given ECT.Materials and Methods:Details of demographic and clinical profile, indications for ECT, response patterns, adverse effects, etc. were recorded.Results:Among all the patients who received ECT,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Studies which have compared the demographic profile of adult patients with BD and schizophrenia in general suggest that, compared to patients with schizophrenia, higher proportion of patients with BD are married. [ 36 37 ] A multinational study, which included participants from India, which evaluated the association of mental disorders with marriage and divorce rates concluded that many mental disorders, including BD, are associated with lower likelihood of ever marrying (odds ratios ranging from 0.6 to 0.9) and higher rates of divorce. [ 38 ] Many other studies also support the findings of shorter duration of marriage among patients with BD.…”
Section: Marital Rates and Marital Failure Rates In Patients With Bipmentioning
confidence: 99%
“…Studies which have compared the demographic profile of adult patients with BD and schizophrenia in general suggest that, compared to patients with schizophrenia, higher proportion of patients with BD are married. [ 36 37 ] A multinational study, which included participants from India, which evaluated the association of mental disorders with marriage and divorce rates concluded that many mental disorders, including BD, are associated with lower likelihood of ever marrying (odds ratios ranging from 0.6 to 0.9) and higher rates of divorce. [ 38 ] Many other studies also support the findings of shorter duration of marriage among patients with BD.…”
Section: Marital Rates and Marital Failure Rates In Patients With Bipmentioning
confidence: 99%
“…Apart from the pharmacological treatments, various nonpharmacological treatments including the neuromodulation techniques and psychosocial interventions are also used frequently. A retrospective review for the period of 10 years was conducted by Bharadwaj et al [ 61 ] in diagnosed cases of bipolar disorder receiving electroconvulsive therapy (ECT) for delineating the clinical profile and outcome of such patients. It was found that among all patients who received ECT, 18% were diagnosed to have bipolar disorder, and the most common indication is mania with psychotic symptoms, followed by severe depression with psychotic symptoms.…”
Section: Resultsmentioning
confidence: 99%
“…It might not be effective in reducing the core negative features, however it makes the patient's behavior manageable and makes life for their caregivers as well as the patient easier. It improves the social functioning of the patient thereby making their lives tolerable [6] .…”
Section: Moderate Intellectual Disability With Psychosis Casesmentioning
confidence: 99%